Modified star-star fractal (MSSF) super-wideband antenna - Singhal S.; Singh A.K. (My University, 2025)
A microstrip line fed star-star fractal antenna with notch loaded semi-elliptical ground plane is presented for super wideband applications. An impedance bandwidth of 4.6–52 GHz, i.e., a bandwidth ratio of 11.31:1 is achieved for VSWR < 2. The antenna structure has advantages of compact dimensions and wider bandwidth over previously reported SWB structures. Radiation characteristics, i.e., co and cross polar radiation patterns, peak gain, and efficiency has been presented and discussed. The simulated and experimental results are found to be good agreement. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:624–630, 2017. © 2017 Wiley Periodicals, Inc.